Neural tube malformations: complex segregation analysis and calculation of recurrence risks. - Lalouel, J M (1979)
Familial data on neural tube malformations in Great Britain were submitted to segregation analysis under the mixed model. Maternal and fetal factors cannot be discriminated in the absence of substantial bodies of data on spina bifida survivors who reproduce or on half-sibs. Early abortion studies would allow differential mortality in utero to be taken into account. After fitting the mixed and generalised single locus models, it is concluded that the multifactorial model can provisionally be used for calculation of recurrence risks. Pathogenic hypotheses implicating twinning seem to rest on little evidence.